Sobre a idade das crises: as inter-relações sujeito-identidade-feminismo na pós-modernidade - Rossi, Aparecido Donizete [UNESP] (My University, 2012)
This essay intends to think critically and theoretically on the interrelations among subject, identity, and Feminism in the context of Postmodernity, a context which will be herein denominated ―Age of Crises. These three aspects will be approached under a Historical perspective and put into question in a philosophical sight guided by Post-structuralistic theories, especially Derridian Deconstruction. In general, the main objective is to reach into a discussion about the undecidable inter-relation between Feminist thinking and Postmodernity, which is one of the configurations of the many contemporary crises. In order to do so, it will be necessary a previous discussion on the postmodern subject and its identity. This discussion will open up the possibility of contextualizing and discussing Feminism inside the intended objective. This discussion will be structured around the word ―crises which, in a compositional relation to the word ―age, will be taken as a synonym for ―Postmodernity and ―contemporary. ―Age of Crises, ―Postmodernity, ―contemporary, and ―Feminism will be words haunted by the phármakon phenomenon, a key aspect for Derridian Deconstruction, which will be the gravitational force that approximates and separates, in an undecidable relation, those signs.

O presente ensaio pretende refletir crítica e teoricamente sobre as interrelações entre sujeito, identidade e Feminismo no contexto da Pós-modernidade, contexto esse aqui denominado, para o que se pretende, ―Idade das Crises. Esses três aspectos serão abordados sob uma perspectiva histórica e problematizados a partir de um olhar filosófico marcadamente pós-estruturalista, na linha da Desconstrução derridiana. No conjunto, o que se objetiva especificamente é chegar a uma discussão da inter-relação indecidível entre pensamento feminista e Pós-modernidade, uma das configurações das diversas crises da contemporaneidade. Para tanto, não é possível refletir sobre um e outro sem uma prévia discussão sobre o sujeito pós-moderno e sua identidade. É essa discussão que permitirá contextualizar e discutir o Feminismo dentro do objetivo proposto. Tal discussão será estruturada em torno da palavra ―crise que, em composição com a palavra ―idade, será tomada como sinônimo de ―pósmodernidade e de ―contemporaneidade. ―Idade das Crises, ―pósmodernidade, ―contemporaneidade e ―Feminismo serão lexemas assombrados pelo fenômeno do phármakon, um dos aspectos-chave do pensamento desconstrucionista derridiano, o qual será a força gravitacional que aproxima e distancia, em uma relação indecidível, os quatro lexemas.
On the age of crisis: the Inter-relations among subject, identity, and feminism in postmodernity
Keywords: Postmodernity; Feminism; Deconstruction; Identity; Subject; Pós-modernidade; Feminismo; Desconstrução; Identidade; Sujeito